Embedded DSP processor design : - Liu, Dake (Morgan Kaufmann/Elsevier, 2008)
Coverage includes design of internal-external data types, application specific instruction sets, micro architectures, including designs for datapath and control path, as well as memory sub systems. Integration and verification of a DSP-ASIP processor are discussed and reinforced with extensive examples.